Implementasi Strategi Pembelajaran Individual Terstruktur bagi Anak Tuna Grahita Ringan di Sekolah Dasar Inklusi - Muh. Syahrul Hadi; Ahmad Zanawi; Zulkarnain (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
Inclusive education is a global mandate that emphasizes the importance of providing education that ensures access, participation, and learning success for all students, including children with special needs (CSN). In this context, children with mild intellectual disabilities present unique challenges, particularly related to limitations in cognitive aspects, social adaptation, and self-regulation. The main issue addressed in this study is how structured individual learning strategies can be effectively implemented to support the achievement of competencies for students with mild intellectual disabilities in inclusive elementary school settings. The aim of this research is to conduct a theoretical review of the effectiveness of the Individualized Education Program (IEP) as a pedagogical approach based on individual needs, responsive to the unique characteristics of learners. The method used is a systematic literature review with a qualitative-descriptive approach through the examination of scientific publications, academic books, and national policies related to inclusive education and differentiated learning services. The analysis results show that the IEP plays a strategic role in optimally accommodating the learning needs of students with mild intellectual disabilities, emphasizing flexible planning, realistic goals, and progress-oriented evaluation. The effectiveness of the IEP increases significantly when it is designed through cross-professional collaboration among general education teachers, special education teachers, and parents. The conclusion of this study affirms that the implementation of IEP not only strengthens the pedagogical dimension of inclusive education but also promotes a paradigm shift towards more adaptive and humanistic education. The novelty of this study lies in the conceptual integration and practical implementation of the IEP for students with mild intellectual disabilities in elementary schools, which remains limited within the scope of national research.